Professional Writing Creative and Critical Approaches - Kesteven, Lisa.; Melrose, Andrew (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book has been designed specifically for students in writing classes and other writers interested in developing proficient writing careers in a professional environment. As professional writing continues to change rapidly alongside digital developments, this book frames professional writing particularly for 'creative' and other writers. The professional world needs writers with a diverse portfolio of skills and capabilities; if writers can master these, they are more able to make a living from their writing and support their more creative endeavours. Each chapter includes a comprehensive range of exercises to build professional skills, along with learning objectives, case studies, worked examples, tips for success, and suggested websites and further reading. Lisa Kesteven is a lecturer on Creative and Professional Writing and has designed and led modules on Professional Writing. As well as being a writer of fiction and non-fiction, Lisa has worked freelance for a number of years and has her own freelancing business. Andrew Melrose is an Emeritus Professor of Critical and Creative writing and a writer. He has over 160 film, fiction, non-fiction, research, songs, poems, chapters and other writing credits, including 15 films and 39 books.
1 Introduction to Professional Writing -- 2 Writing for Business -- 3 A Career in Professional Writing -- 4 The Art of Communication and the Freelancer -- 5 Writing for an Online Market -- 6 Self Promotion -- 7 Finding Work -- 8 Navigating the Bid Process on Freelancing Platforms -- 9 Estimating Writing Projects -- 10 Planning and Managing Writing Projects -- 11 The Editing Process -- 12 Building a Successful Career as a Professional Writer.
Keywords: Creative writing; Penmanship; Career education; Creative Writing; Writing Skills; Career Skills